Integrasi Cost–Benefit Analysis dalam Penilaian Ekonomi Ekosistem dan Sumber Daya Alam : Tinjauan Kritis Literatur Global - Darmawansyah Darmawansyah; Reflis Reflis; Mustopa Romdhon; Satria Putra Utama (Jurnal Manajemen Bisnis Digital Terkini, 2026)
The economic valuation of natural resources (NR) is an important instrument in supporting evidence-based decision-making, particularly in sustainable environmental management. Cost–Benefit Analysis (CBA) serves as a primary approach to assess the economic feasibility of programs or policies by integrating all benefits and costs, including non-market values. This article presents a systematic literature review of studies employing CBA for NR valuation during the period 2010–2024, based on searches in Scopus, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis, and Google Scholar, using stringent selection criteria. The review findings indicate that CBA has been widely applied in forest management, biodiversity conservation, land rehabilitation, water and air pollution control, and ecotourism development, providing a quantitative depiction of economic feasibility through indicators such as Net Present Value (NPV), Benefit–Cost Ratio (BCR), and Internal Rate of Return (IRR). Key challenges were identified in non-market valuation, long-term uncertainty, data limitations, and sensitivity to discount rate assumptions. These findings underscore the importance of integrating environmental valuation methods, conducting comprehensive sensitivity analyses, and adopting multidisciplinary approaches to strengthen the application of CBA in sustainable NR management, while also offering strategic recommendations and directions for future research for policymakers and environmental economics scholars.